Pengaruh Efikasi Diri Keuangan dan Pembelian Impulsif Terhadap Perilaku Kredit Berisiko Pengguna Shopee Paylater Ibu Rumah Tangga Perumahan Jomin Estate - Elizabeth Margareta Wijaya; Ujang Suherman; Thomas Nadeak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research examines the influence of financial self-efficacy and impulsive buying on risky credit behavior among housewives who use Shopee PayLater in the Jomin Estate housing complex. A quantitative descriptive–verificative design was applied with 136 respondents. Data were analyzed using multiple linear regression via SPSS version 26. The findings indicate that financial self-efficacy exerts a positive and significant effect on risky credit behavior, suggesting that greater confidence in financial management may increase engagement with higher-risk digital credit. Impulsive buying also shows a positive and significant effect, implying that unplanned purchasing intensifies credit risk. Jointly, both variables explain 59.6% of the variance in risky credit behavior. These results underscore the role of psychological and consumer behavior factors and provide empirical insights into Buy Now Pay Later usage, informing efforts to promote more responsible digital credit management.